CGIAR System Internal Audit Function Strategy - CGIAR System Organization (CGIAR System Organization, 2018)
This document sets out Internal Audit Function's vision, mission, value proposition, objectives, and the strategies to achieve the objectives. The document also outlines main activities to be implemented in 2018 and beyond as part of the strategy.